From thin to extra-thick adhesive layer thicknesses: fracture of bonded joints under mode I loading conditions - Romina Fernandes; S. (Sofia) Teixeira de Freitas; M.K. (Michal) Budzik; J.A. (Johannes) Poulis; R. (Rinze) Benedictus (4TU.Centre for Research Data, 2019)
Purpose of the test campaign: the purpose of these experiments was to investigate the effect of adhesive bond line thickness on mode I fracture behaviour of steel-steel bonded joints. The Double Cantilever Beam (DCB) specimens with different adhesive bond lines were tested.
Test equipment: all tests were performed on a 20 kN tensile test machine. The crack length was measured by means of a Digital Image Correlation (DIC) system or a camera system. The applied force and displacement were measured by the tensile test machine, and also sent as inputs to the Digital Image Correlation (DIC) system or to the camera, in order to facilitate synchronization of the data.
Keywords: Materials Engineering; Mechanical Engineering; Adhesive joints; Composites; Delamination; Extra-thick bond lines; Fracture toughness; Mode I; dissertation